Artificialized land and land take - Desrousseaux, Maylis; Béchet, Béatrice; Le Bissonnais, Yves; Ruas, Anne; Schmitt, Bertrand (éditions Quae, 2020)
Considered as one of the main factors in erosion of the biodiversity, land take describes the global reduction in the proportion of land allocated to farming and forestry or to natural spaces. This work identifies the decisive economic and social factors in land take and its impact on the environment and agriculture. It suggests levers of action likely to limit its development and its negative effects.